UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI MOTIVASI GURU - Yastuti, Dianda Fuji; Suwatno, Suwatno (Universitas Pendidikan Indonesia, 2017)
This article reviews the role of the teacher as motivator expected effect on student learning outcomes. Depends on the result of data analysis using simple regression analysis survey method with using 90 questionnaires X class students in office administration productive subject in SMK Bandung Regency. The result of analyst describe that role of teacher as motivator is significant influence to student learning outcome in subject of productive office administrator in SMK Bandung Regency. So implication of the result of study is meaning to improve the student learning outcome by motivation of teacher. Therefore teacher has to improving student interesting one of which by giving motivation to student for improving the quality of learning.ABSTRAKTulisan ini mengkaji tentang peran guru sebagai motivator yang diduga kuat mempengaruhi hasil belajar siswa. Berdasarkan hasil analisis data menggunakan analisis regresi sederhana metode survey dengan menggunakan angket sebanyak 90 siswa kelas X pada mata pelajaran produktif Administrasi Perkantoran pada salah satu SMK di Kabupaten Bandung. Hasil analisis data menunjukkan bahwa peran guru sebagai motivator terdapat pengaruh signifikan terhadap hasil belajar siswa pada mata pelajaran produktif Administrasi Perkantoran. Dengan demikian implikasi hasil kajian tersebut adalah bahwa upaya meningkatkan hasil belajar siswa melalui motivasi guru. Untuk itu guru haruslah meningkatkan minat siswa yang salah satunya melalui pemberian motivasi kepada siswa agar meningkatkan kualitas pembelajaran.